Literature Review: Misconception Analysis of Static Fluid Material in High School Students - Amrullah, Lalu Azikri; Handrianto, Handrianto; Busyairi, Ahmad (Prodi Fisika FKIP Unram, 2024)
This article presents a literature review on misconceptions of static fluid material in high school students, which is an important issue in physics learning. These misconceptions often stem from improper understanding of basic concepts, which can hinder students' academic achievement. Research shows that students often misunderstand key concepts such as hydrostatic pressure, Pascal's law and Archimedes' law, which negatively impacts their understanding of more complex physical phenomena. Through an in-depth analysis of 348 Google Scholar indexed publications from 2015 to 2024 with help from search tools such as Publish or Perish and Dimensions AI. This article identifies the causes of misconceptions and offers a constructivist approach as a solution to improve student understanding. By integrating findings from various studies, this review aims to provide a more comprehensive insight into the phenomenon of misconceptions and the strategies that can be applied to overcome them, so as to improve the effectiveness of physics learning at the high school level. Keywords: Misconceptions; Physics Materials; Static Fluid; High School Students.